THE DAILY AS A SOURCE OF INFORMATION FOR THE CHOICE OF RESEARCH ISSUES IN HEALTH SCIENCES (PART V) - Balarezo-López, Gunther (2022)
Scientific research not only consists of the design and development of the project, data collection, analysis of results and preparation of the final report. Also part of this process is the publication to disseminate the results obtained in a scientific journal. In this sense, the objective was to continue with the fifth installment of the review of news published in various parts of the world in the Diario El Comercio (Lima, Peru), which were related to health. Unfortunately, in many cases researchers have not developed the skills to write adequately for their work to be accepted in journals. The problem arises when an investigation does not publish its results because it can be considered as an investigation that was not carried out. Keywords: diary – health sciences – scientific article – scientific journal – scientific publication